Borate bioactive glass prevents zoledronate‐induced osteonecrosis of the jaw by restoring osteogenesis and angiogenesis. (16th June 2020) - Su, Zhifei; Li, Jiehang; Bai, Xuan; Tay, Franklin R.; Zhang, Min; Liang, Kunneng; He, Libang; Yuan, He; Li, Jiyao
Abstract: Objectives: Bisphosphonate‐related osteonecrosis of the jaw (BRONJ) is a severe complication of systemic nitrogen‐containing bisphosphonate (N‐BP) administration, which leads to osteonecrosis, pain, and infection. Despite much effort, effective remedies are yet to be established. This study aimed to investigate potential recovery effect of borate bioactive glass (BBG) in vitro and in vivo. Methods: The effect of BBG on zoledronate‐treated bone marrow mesenchymal cells (BMSCs) and human umbilical vein endothelial cells (HUVECs) was explored by cell counting kit‐8, EdU assay, flow cytometry, alkaline phosphatase staining, alizarin red staining, angiogenesis experiment, and real‐time quantitative polymerase chain reaction. The preventive effect of BBG on zoledronate‐induced osteonecrosis of the jaw in rat model was examined by micro‐CT, HE staining, and immunohistochemistry. Results: Exposure of BBG to BMSCs and HUVECs increased cell proliferation and restored their osteogenesis and angiogenesis potential in vitro. The BRONJ lesions were satisfactorily repaired and bone mineral density, bone volume/tissue volume, trabecula number, OCN‐positive cells, and CD31‐positive cells were increased in the BBG‐treated groups compared with saline‐treated groups. Conclusions: Exposure of BMSCs and HUVECs to BBG restores osteogenesis and angiogenesis inhibited by zoledronate. BBG successfully restores extraction socket healing of BRONJ in rat model.